2019
DOI: 10.3389/fmed.2019.00034
|View full text |Cite
|
Sign up to set email alerts
|

From Big Data to Precision Medicine

Abstract: For over a decade the term “Big data” has been used to describe the rapid increase in volume, variety and velocity of information available, not just in medical research but in almost every aspect of our lives. As scientists, we now have the capacity to rapidly generate, store and analyse data that, only a few years ago, would have taken many years to compile. However, “Big data” no longer means what it once did. The term has expanded and now refers not to just large data volume, but to our increasing ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
229
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(257 citation statements)
references
References 66 publications
1
229
0
3
Order By: Relevance
“…In addition, limited activity in kidney research has impacted the evidence base for the treatment of kidney diseases, resulting in a lack of useful surrogate end-points for progression from the early stages of kidney disease-hindered trials [14,15]. On the same note, a great amount of cohort data could also be applied in generating relevant hypotheses and provide major insights into the etiology, pathogenesis, and prognosis of kidney diseases [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, limited activity in kidney research has impacted the evidence base for the treatment of kidney diseases, resulting in a lack of useful surrogate end-points for progression from the early stages of kidney disease-hindered trials [14,15]. On the same note, a great amount of cohort data could also be applied in generating relevant hypotheses and provide major insights into the etiology, pathogenesis, and prognosis of kidney diseases [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies demonstrated that even the positioning of applied parts (e.g., probes, sensors) in a trial might affect the significance of the results 10 . Therefore, pursuing a precision medicine approach in trialling deep learning (DL)-based medical technologies requires particular attention in the way the study is designed, executed and its results analysed [11][12][13] .…”
mentioning
confidence: 99%
“…Big data and machine learning are redefining healthcare goals for the future. Healthcare data are impacting the way disease research is performed, and the level of complexity in population health management is increasing as the traditional fee for service approach is transformed into the value-based care model [17,18].…”
Section: Why Big Data and Machine Learning?mentioning
confidence: 99%